Oil Price and Inflation in Iran: Non-Linear ARDL Approach - Davari, Hamid; Kamalian, Alireza (International Journal of Energy Economics and Policy, 2018)
In this paper we study the relationship between oil price (or revenue) changes and inflation rate in Iran seasonally in 2003-2015. Method of the study was able to identify asymmetry of oil price and inflation which is recognized as nonlinear autoregressive distributed lag model. Estimated model clarified nonlinear effect of oil price on inflation. Clearly, we found out that there was significant relationship between the reduction in oil price and inflation growth while there was no significant relationship between increase in oil price growth and inflation rate. Keywords: inflation behavior, oil price, asymmetry JEL Classifications: E31, Q4